LIPID-COMPOSITION OF NIPPLE DISCHARGES OF WOMEN WITH GALACTORRHEA - (:unkn) unknown (PARTHENON PUBLISHING GROUP, 1994)
The biochemical nature of nipple discharge, including galactorrhea, and the physiology of lactation in patients with nipple discharge have not been studied extensively. Studies of the composition of nipple discharges may provide further insight into the complex processes involved in their secretion. In this study we compared the lipid composition of nipple discharges from patients with galactorrhea with that of human colostrum. The diagnosis of galactorrhea was confirmed by the presence of casein, detected by the anti-casein radial immunodiffusion test. Triglyceride, cholesterol and phospholipid levels in the nipple discharge samples were quite high compared with the colostrum samples. The proportion of 6:0 and 22:1 fatty acids was lower in the discharge samples and the proportion of 18:2 and 20:4 fatty acids was higher. Levels of phospholipid and neutral lipids, determined by quantitative densitometry in situ after separation by thin layer chromatography, also varied between discharge and colostrum, with a higher level of free fatty acids and triglyceride fractions in the nipple discharge. The lipoprotein electrophoretic bands of the nipple discharge samples resembled serum lipoprotein bands while colostrum samples gave no bands on electrophoresis.
Keywords: NIPPLE DISCHARGE; LIPID COMPOSITION; COLOSTRUM